APAKAH PAJAK, MEKANISME BONUS DAN TUNNELING INCENTIVE DAPAT MEMPENGARUHI PRAKTIK TRANSFER PRICING? - Patriandari Patriandari; Mutia Cahya (AKRUAL : Jurnal Akuntansi dan Keuangan, 2020)
The purpose of this study is to obtain empirical evidence on "The Effect of Taxes, Bonus Mechanisms and Tunneling Incentives on Transfer Pricing Practices in Manufacturing Companies in the Consumer Goods Industry Listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period and obtained 18 samples from 56 companies. . The data analysis method uses multiple linear regression with SPSS version 26. The results of this study indicate that taxes and income have a positive effect on transfer pricing practices and tunneling incentives have no significant effect on transfer pricing practices.